Reconstruction and analysis of highest energy γ-rays and its application to pulsar wind nebulae - Joshi, Vikas (2019)
Abstract: The High Altitude Water Cherenkov (HAWC) γ-ray observatory detects cosmic- and γ-rays in the TeV energy range. HAWC was recently upgraded with a sparse detector array (the outrigger array), which increases the instrumented area by a factor of 4-5 and will improve the sensitivity at energies greater than 10 TeV. This thesis consists of a number of contributions towards the improvement of the performance of HAWC at the highest energies and the study of a prominent high energy source, 2HWC J2019+367. To decide on components of the outrigger array, simulation input is provided. A new Monte Carlo template-based reconstruction method for air shower arrays is developed. It reconstructs the core location and energy of γ-ray showers. The goodness of fit of the method is utilised to separate the cosmic- and γ-ray showers. This method significantly improves the HAWC shower reconstruction and combines the reconstruction of HAWC and the outrigger array. In-depth spectral and morphological studies of 2HWC J2019+367 are performed. 2HWC J2019+367 shows a hint of energy-dependent morphology. A new HAWC source is discovered in the vicinity associated with VER J2016+371. The preferred direction of the X-ray and TeV emission indicates their association, and their combined spectral modelling show that 2HWC J2019+367 is likely to be the TeV pulsar wind nebula of PSR J2021+3651.
Keywords: Hochschulschrift